2022
DOI: 10.3390/molecules27134084
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Compounds in Organic and Conventional Fermented Food

Abstract: Compared to conventional agriculture, organic farming is believed to provide a higher nutritional and health value in its products due to the elimination of harmful contaminants (pesticides, nitrates, heavy metals, etc.). Numerous studies have been conducted to show how the production system affects the quality of food in terms of the content of bioactive compounds. The aim of this study was to compare the content of some bioactive compounds (vitamin C, β-carotene, Ca content) and lactic acid bacteria (LAB) nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The bioactive component in fermented foods may differ from the raw materials (Breza‐Boruta et al ., 2022). Carotenoids are a group of bioactive tetraterpenoids that exhibit antioxidant properties (Garrido‐Fernández et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive component in fermented foods may differ from the raw materials (Breza‐Boruta et al ., 2022). Carotenoids are a group of bioactive tetraterpenoids that exhibit antioxidant properties (Garrido‐Fernández et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The bioactive component in fermented foods may differ from the raw materials (Breza-Boruta et al, 2022).…”
Section: Carotenoid Profiles In Fermented and Unfermented Spl Smoothiesmentioning
confidence: 99%
“…Retention times of different forms of quercetin have been found to be different. 50,51 Both free quercetin and released quercetin also show characteristic UV−vis peaks at 376 nm. The peak around 370 nm has been attributed to the neutral form of quercetin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Fermentation processes, which also attracted medical, biomedical, and research communities (Choi et al, 2022;Cui et al, 2022;Żółkiewicz et al, 2020), have been shown to have very low water and carbon footprints or land use requirements compared to conventional food production, and the effectiveness of post-biotics especially anti-inflammatory, immunomodulatory, and anti-cancer properties has been presented (Żółkiewicz et al, 2020). Effects of food fermentation include increased bacteriocin genetic potential against pathogens and removal of non-nutrients; partial degradation of toxic or harmful substances; and generation of biologically active components such as anti-oxidants, antimicrobial, anti-allergic, or anti-inflammatory compounds (Breza-Boruta et al, 2022;Kelly et al, 2022;Şanlier et al, 2019). New raw materials for fermentation processes can include food wastes, algae, insects, and so on, and the estimated 1000-2500 edible mushrooms (from estimated total of 140,000) offer a wide range of product opportunities.…”
Section: Fermentationmentioning
confidence: 99%
“…Effects of food fermentation include increased bacteriocin genetic potential against pathogens and removal of non‐nutrients; partial degradation of toxic or harmful substances; and generation of biologically active components such as anti‐oxidants, antimicrobial, anti‐allergic, or anti‐inflammatory compounds (Breza‐Boruta et al., 2022; Kelly et al., 2022; Şanlier et al., 2019). New raw materials for fermentation processes can include food wastes, algae, insects, and so on, and the estimated 1000–2500 edible mushrooms (from estimated total of 140,000) offer a wide range of product opportunities.…”
Section: Resilient Food Technologiesmentioning
confidence: 99%